Effects of titanium oxide coating on the antimicrobial properties, surface characteristics, and cytotoxicity of orthodontic brackets - A systematic review and meta analysis of in-vitro studies - Lichi Ashwin Solanki; S.P. Saravana Dinesh; Ravindra Kumar Jain; Arthi Balasubramaniam (Elsevier, 2023)
Objective: The objective of this review is to systematically analyze the available literature on the effects of titanium oxide (TiO₂) coating on the antimicrobial properties, surface characteristics, and cytotoxicity of orthodontic brackets. Methods: In-vitro studies reporting on the effects of Titanium oxide (TiO₂) coatings on antimicrobial properties, surface roughness, cytotoxic activity and bacterial adhesion of orthodontic brackets were included in the review. Electronic databases such as PubMed, SCOPUS, Web of Science and Google Scholar, were searched till September 2022. Risk of Bias was analyzed by using RoBDEMAT tool. Meta-analysis using Random Effects Model was performed for assessing the antimicrobial activity against S. mutans, C. albicans and L. Acidophilus. Results: A total of 11 studies were included the RoB analysis revealed sufficient reporting across all the domains and inconsistent reporting in only two of the domains. On qualitative analysis, a significant antimicrobial effect of TiO2 coating on orthodontic brackets against Streptococcus mutans, Candida albicans and Lactobacillus acidophilus was reported. The meta analysis revealed a significant overall antimicrobial effect with a high heterogeneity. (SMD: 3.5; p < 0.00001; i2 - 99.2%) Conclusion: An overall significant antimicrobial effect of TiO₂ coated brackets against S. mutans, L. Acidophilus, C. Albicans was noted but with a high heterogeneity. The subgroup analysis revealed a significant antimicrobial effect on C albicans with a low heterogeneity but it was limited by a publication bias. The included studies reported reduced surface roughness, minimal bacterial adhesion and less cytotoxic activity with TiO₂ coated brackets than uncoated brackets.